KAJIAN PENERAPAN CORPORATE UNIVERSITY DALAM PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA APARATUR SIPIL NEGARA - Victor Tulus Pangapoi Sidabutar (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
The ease of doing business in Indonesia in 2019 has increased but the ranking only represents Jakarta and Surabaya and the overall value of Indonesia's competitiveness is still below expectations to attract foreign investors. This is because public organizations in Indonesia are considered inefficient, bureaucratic, less transparent, and have a high level of corruption. In terms of competence, there are differences in the ability of the State Civil Service Apparatus (ASN) in each region so that it is necessary to increase the ability of ASN to be able to deal with changes and developments in the world that is growing so fast and more rapidly. This is where the important role of ASN’s training units in the development of Human Resources (HR) in producing